Diversity of mtDNA in Southern River Otter (Lontra provocax) from Argentinean Patagonia - Centron, Daniela; Ramírez, Benjamín Alejandro; Fasola, Laura; Macdonald, David W.; Chehébar, Claudio; Schiavini, Adrian Carlos Miguel; Cassini, Marcelo Hernan (Journal of Heredity)
Lontra provocax is an endemic species from Patagonia that has been categorized as “endangered” by the International Union for Conservation of Nature. In this study, noninvasive molecular methods were used to investigate the genetic diversity and haplotype distribution of L. provocax in Argentinean Patagonia. We analyzed 150 scat samples collected from 1995 to 2006 and obtained 13 sequences of control region with 1 haplotype and 34 sequences of cytochrome b with 4 haplotypes. The population of the south of Patagonia (Tierra del Fuego and De los Estados Island) showed a relatively high haplotype diversity (h = 0.71) and was statistically different to the population of the north (analysis of molecular variance, FST = 0.15, P = 0.018). We concluded that there are 2 different subpopulations of L. provocax that deserve conservation attention and that the southern population appears not to have suffered a human-induced population bottleneck of the sort typically experienced by various otter species around the world. Fil: Centron, Daniela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Investigaciones en Microbiología y Parasitología Médica. Universidad de Buenos Aires. Facultad de Medicina. Instituto de Investigaciones en Microbiología y Parasitología Médica; Argentina Fil: Ramírez, Benjamín Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Investigaciones en Microbiología y Parasitología Médica. Universidad de Buenos Aires. Facultad de Medicina. Instituto de Investigaciones en Microbiología y Parasitología Médica; Argentina Fil: Fasola, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Macdonald, David W. University of Oxford; Reino Unido Fil: Chehébar, Claudio. Administración de Parques Nacionales; Argentina Fil: Schiavini, Adrian Carlos Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral ...